Effect of the implementation of a solid waste management model in the reduction of health risks in smaller health care centers - Nuevo Chimbote - Rondán Ramos, Jorge Damian (2018)
The generation of hazardous solid waste (puncturing, not puncturing, special and common), by the minor health care centers such as dental clinics, veterinarians, doctors' offices and pharmacies and their inadequate management, causes a serious problem towards human health and the ambient. In the district of Nuevo Chimbote, which has 110 such establishments, the negative impact of this activity has led to the implementation of a specific and integral management model.The characterization of these residues allowed to generate indicators that support its implementation.The methodology used for the development of the management model was developed taking into account the legal requirements of the sector and empirical elements, based on the analysis of Benchmarking, which relates good practices and national and international experiences in the management of solid waste in order to take into account the needs and expectations of the interested parties.The proposed model of solid waste management proposed and implemented contributed to reduce the health risks of these establishments: the pharmacies and veterinary clinics were the establishments that initially presented a higher sanitary risk (51.67% and 47.50%) due to the inadequate management of the hazardous solid waste sharps in the stages of storage, treatment and final disposal, after the implementation the risk decreased to 15.83% and 23.89% respectively.In both the medical offices and dental clinics, which initially had a health risk of 38.75%, reaching a health risk of 7.5%.